Primary oral health care: Reason for seeking treatment for oral health problems at three primary care clinics of Kuantan, Pahang, Malaysia - Md Aris, Mohd Aznan; Tin, Myo Han; Sulong, Robiatu Adawiyah (2013)
Background: A limited oral health personnel who engage most in secondary care is one of the challenges to provide primary oral health care including oral health promotion and emergency care in primary care setting.1In Malaysia-Myanmar comparative study (2012), a range of magnitude of oral health problems (OHPs) in primary care clinics was 1 to 6.5/1000/month.2 Reasons for seeking treatment for OHPs at primary care clinics may relate with awareness of the patients on oral health services. Objectives: To assess relationship between the reasons for taking treatment for oral health problems at primary care clinics and awareness of the patients on oral health care services nearby their residence. Methods: Total 77 patients with OHPs who attended at 3 primary care clinics - University Primary Care Clinic, International Islamic University, (IIUM-Kuantan Campus), Public Primary Care Clinic (KK Balok) and Private clinic (Polyclinic Ar Razi)- in Kuantan, Malaysia, participated willingly in the study from 1st April to 31st July 2012. A pre-tested structured questionnaire with open-ended questions was used to collect the data. A cross analysis was done between types of clinics and in terms of reasons for seeking treatment at primary care clinics and their awareness on oral health services nearby residence. Association between reason for seeking treatment at primary care clinics and awareness on oral health services was also analysed. Findings: Although, 56% of the reasons for seeking treatment for oral health problems at primary care clinics were non-specific answers same as reason for encounters, significant answers reflecting nature of primary care practices such as easily accessibility to primary care clinics (17%), preferring to and requiring services provided by primary care physicians because of co-morbidity with medical diseases (12%) and getting emergency services (5%) were noticed. A significant differences (p<0.05) between the patients from 3 primary care clinics and their awareness on existing dental clinic, types of dental clinics and clinic opening hours and day was found; but it was not significant (p>0.05) in knowing dentists and dental nurses. The association between the reasons for seeking treatment for OHPs at primary care clinics and awareness of the oral health services was not statistically significant (p>0.05). Conclusion: This study indicated that primary care physicians may play one of key partners for oral health promotion, prevention & emergency oral health care because of co-morbidities with medical diseases and nature of practices. Activities to promote awareness on oral health services and coordinated care between primary care physicians and oral health practitioners should be promoted to provide holistic care to the patients. Key words: oral health problems, reasons for seeking treatment, primary care clinics